2018
DOI: 10.3389/fimmu.2018.00257
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Phenotypic Changes of Natural Killer Cells in Whole Blood during Mycobacterium tuberculosis Infection and Disease

Abstract: Tuberculosis (TB) is still a global health concern, especially in resource-poor countries such as The Gambia. Defining protective immunity to TB is challenging: its pathogenesis is complex and involves several cellular components of the immune system. Recent works in vaccine development suggest important roles of the innate immunity in natural protection to TB, including natural killer (NK) cells. NK cells mediate cellular cytotoxicity and cytokine signaling in response to Mycobacterium tuberculosis (Mtb). NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 94 publications
9
48
1
Order By: Relevance
“…NK cells are recruited to the lung in patients with active TB disease (Portevin et al, 2012). However, NK cells circulating in peripheral blood of patients with pulmonary TB disease exhibit decreased IFN-γ production capacity (Bozzano et al, 2009;Garand et al, 2018), which is partially restored following anti-TB treatment (Nirmala et al, 2001), thus suggesting an association between NK cell functional capacity and bacterial load. Moreover, longitudinal cohort studies have indicated that progression to active TB disease is preceded by a decline in the frequency of circulating NK cells, which is restored following successful treatment for active TB (Roy Chowdhury et al, 2018), thus providing further evidence of an important role for NK cells in Mtb infection and TB disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells are recruited to the lung in patients with active TB disease (Portevin et al, 2012). However, NK cells circulating in peripheral blood of patients with pulmonary TB disease exhibit decreased IFN-γ production capacity (Bozzano et al, 2009;Garand et al, 2018), which is partially restored following anti-TB treatment (Nirmala et al, 2001), thus suggesting an association between NK cell functional capacity and bacterial load. Moreover, longitudinal cohort studies have indicated that progression to active TB disease is preceded by a decline in the frequency of circulating NK cells, which is restored following successful treatment for active TB (Roy Chowdhury et al, 2018), thus providing further evidence of an important role for NK cells in Mtb infection and TB disease in humans.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, NK cells can be found in lung tissue specimens from patients with chronic Mtb infection (78), suggesting their involvement in TB pathogenesis. Current evidence suggests a beneficial role of NK cells during human TB as changes in their immunophenotype and function are associated with the development of active TB (79)(80)(81)(82)(83)(84)(85)(86)(87)(88). NK cells support the activity of CD8+ T cells during Mtb infection (89), shape the maturation process and Mtb-antigen processing in dendritic cells (DCs) (90), limit the expansion of regulatory CD25+ T cells (91), and even participate in the mechanisms underlying protection induced by BCG vaccination (92).…”
Section: Nk Cell Memory In Tbmentioning
confidence: 99%
“…NK cells form a substantial part of the innate immune response generated from this vaccine, and produce inflammatory cytokines in response to infection [63]. Although understanding of NK cell function during Mycobacteria infection is limited, NK cells in the Mtb granuloma exert cytotoxic pressure through production of granulysin and perforin [64], as well as restriction of bacterial growth through direct contact with infected cells via cytotoxic NKG2D + NK cells [32]. HLA-E : Mtb peptide complexes are not recognized by CD94/NKG2 molecules, so do not control activation or inhibition of NK cells through these receptors [65].…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%